2018
DOI: 10.1074/jbc.ra118.002983
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer of zeste homolog 2 (Ezh2) controls bone formation and cell cycle progression during osteogenesis in mice

Abstract: Epigenetic mechanisms control skeletal development and osteoblast differentiation. Pharmacological inhibition of the histone 3 Lys-27 (H3K27) methyltransferase enhancer of zeste homolog 2 (EZH2) in WT mice enhances osteogenesis and stimulates bone formation. However, conditional genetic loss of early in the mesenchymal lineage ( through excision via promoter-driven Cre) causes skeletal abnormalities due to patterning defects. Here, we addressed the key question of whether controls osteoblastogenesis at later d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(71 citation statements)
references
References 65 publications
5
66
0
Order By: Relevance
“…Complete knockout of EZH2 in mice produced nonviable embryos with abnormal accumulation of mesodermal cells . EZH2 also has key roles in skeletal development as conditional loss of EZH2 , affects skeletal patterning as well as skeletal growth and bone formation . For example, conditional loss of EZH2 in neural crest–derived tissues (using the Wnt1‐Cre driver) causes craniofacial defects .…”
Section: The Basics Of Epigeneticsmentioning
confidence: 99%
See 2 more Smart Citations
“…Complete knockout of EZH2 in mice produced nonviable embryos with abnormal accumulation of mesodermal cells . EZH2 also has key roles in skeletal development as conditional loss of EZH2 , affects skeletal patterning as well as skeletal growth and bone formation . For example, conditional loss of EZH2 in neural crest–derived tissues (using the Wnt1‐Cre driver) causes craniofacial defects .…”
Section: The Basics Of Epigeneticsmentioning
confidence: 99%
“…These mice also have distinct skeletal phenotypes during postnatal endochondral bone formation . Loss of EZH2 in osteoblasts (using the SP7/Osx1‐Cre driver) causes a transient low bone mass phenotype that recedes by the time the mice reach skeletal maturity . Studies on the EZH2 null mutation in chondrocytes (using the COL2a1‐Cre driver) revealed that EZH2 deficiency reduces H3K27me3 levels, yet remarkably had minimal impact on skeletal development or maturation of articular cartilage .…”
Section: The Basics Of Epigeneticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with these studies, previous work from our laboratories revealed that EZH2 suppresses osteogenesis and promotes adipogenesis in BMSCs . Furthermore, we found that EZH2 is required for normal cell cycle progression in BMSCs and that inhibition of EZH2 blocks cell proliferation by de‐repressing cell cycle inhibitors . Thus, self‐renewal and lineage commitment of BMSCs is tightly linked to EZH2 function.…”
Section: Introductionmentioning
confidence: 99%
“…However, conflicting results on Ezh2 expression and function in pre-osteoblasts were also reported recently, Dudakovic et al published data showing that Ezh2 cko expressing the Osx-Cre driver have no changes on bone volume phenotype in young adult mice. 43 Possible explanation for that may be as follows: (i) age, animal age presented in our study was younger, deletion of Ezh2 in pre-osteoblast leads to aberrant skeletal growth in different age of mice; (ii) sample size, we only presented four animals per group as a pilot study, our original purpose was to check if SATB2 gene expression changes in bone in pre-osteoblast specific Ezh2 deletion; (iii) different methods, we used pQCT to measure bone density, although we used micro-CT method, we had some failed and did not present in the current report; and (iv) different Cre mouse model used and different control mouse groups were compared. Nonetheless, from results of our current study, it was indicated once again that bone development or growth is epigenetically regulated.…”
Section: Discussionmentioning
confidence: 99%